Covalent Immobilization of Candida antarctica Lipase B on Functionalized Hollow Mesoporous Silica Nanoparticles. Issue 14 (14th April 2021) - Zhong, Lijuan; He, Caiyun; Xiao, Chunyan; Yao, Chuanyi; Pyatt, Ian Howard; Lu, Yinghua
Abstract: Candida antarctica lipase B (CALB) produced by recombinant Pichia pastoris was covalently immobilized to a carboxyl‐functionalized hollow mesoporous silica sphere (HMS) synthesized by sol‐gel precipitation. The HMS was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X‐ray diffractometer (XRD), and Brunauer‐Emmett‐Teller (BET). The immobilized CALB was characterized through Fourier transform infrared spectra (FT‐IR) and elemental analysis to verify the binding of enzyme. The free and immobilized CALB were tested in tributyrin hydrolysis. Results revealed that CALB loading capacity of HMS‐COOH was about 28.6 mg/g support and the corresponding enzyme activity was up to about 2700 U/g support at optimal pH and temperature, which was 6.5 and 30 °C respectively. Moreover, compared with free CALB, the immobilized CALB presented more resistant towards the reaction pH and temperature changes. Furthermore, the immobilized CALB retained 60 % residual activity after eight batches of recycling and exhibited better thermal stability and storage stability, which was promising in the potential industrial applications. Abstract : An efficient method for convalent immobilization of CALB was developed by conjugation to functionalized HMS via amide bonds, with eco‐friendly, efficient, and easy operation conditions. Compared with free CALB, immobilized CALB presented more resistant towards the reaction pH and temperature changes. The immobilized CALB retained 60 % residual activity after eight batches of recycling and exhibited improved thermal stability and storage stability